Survival benefit of neoadjuvant hepatic arterial infusion chemotherapy followed by hepatectomy for hepatocellular carcinoma with portal vein tumor thrombus - Hu, Zili; Yang, Zhenyun; Wang, Jiongliang; Fu, Yizhen; Hu, Zhiwen; Zhou, Zhongguo; Chen, Minshan; Zhang, Yaojun (Frontiers in Pharmacology, 2023)
background/purpose: The prognosis of hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) is generally poor and hepatectomy is optional for these patients. This study aims to explore the survival benefits of neoadjuvant hepatic arterial infusion chemotherapy (HAIC) for resectable HCC with PVTT.Methods: This retrospective study included 120 resectable HCC patients with PVTT who underwent hepatectomy, from January 2017 to January 2021 at Sun Yat-sen University Cancer Center. Of these patients, the overall survival (OS) and recurrencefree survival (RFS) of 55 patients who received hepatectomy alone (Surgery group) and 65 patients who received neoadjuvant HAIC followed by hepatectomy (HAIC-Surgery group) were compared. Logistic regression analysis was conducted to develop a model predicting the response to neoadjuvant HAIC.The OS rates for the HAIC-Surgery group at 1, 3, and 5 years were 94.9%, 78% and 66.4%, respectively, compared with 84.6%, 47.6% and 37.2% in the Surgery group (P < 0.001). The RFS rates were 88.7%, 56.2% and 38.6% versus 84.9%, 38.3% and 22.6% (P = 0.002). The subgroup analysis revealed that the survival benefit of neoadjuvant HAIC was limited to patients who responded to it. The logistic model, 3 consisting of AFP and CRP, that predicted the response to neoadjuvant HAIC performed well, with an area under the ROC curve (AUC) of 0.756.Neoadjuvant HAIC followed by hepatectomy is associated with a longer survival outcome than hepatectomy alone for HCC patients with PVTT and the survival benefit is limited to patients who respond to neoadjuvant FOLFOX-HAIC.